Postpolymerization synthesis of (bis)amide (co)polymers: Thermoresponsive behavior and self-association - Zhu, Y.; Lowe, A.; Roth, Peter (Elsevier Ltd, 2014)
A library of novel well-defined (bis)amide-based (co)polymers was prepared through postpolymerization modification of poly(pentafluorophenyl acrylate) with amines including ammonia and amide derivatives of amino acids. Products were characterized using a combination of NMR and FT-IR spectroscopies and size exclusion chromatography; results conformed to the expected structures obtained through quantitative conversion. The series of (bis)amide (co)polymers displayed rich phase behavior in aqueous solution such as thermoreversible gelation at low temperature and high concentration while other samples displayed inverse temperature dependent solubility (lower critical solution temperature (LCST)-type) behavior. A hydrophobically modified polyacrylamide copolymer displayed upper critical solution temperature (UCST) behavior in aqueous solution. Significantly, driven by polymer–polymer hydrogen bonding, copolymers self-associated into highly ordered, regular structures of several tens to hundreds of micrometers in size. Morphologies included sheet-like, rod-like and honeycomb-like structures and depended strongly on the chemical composition of copolymers.